Современная концепция развития промышленной ботаники - Глухов, А.З.; Хархота, А.И. (Промышленная ботаника, 2006)
The article presents sources of industry botany as a department of botanical attainments. Existent notions about industry botany content are synthesized and retreatment of its conception, subject and character of investigations are given. Main directions for the development, problems, and tasks of industry botany on present-day stage are defined.